Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1016/0014-3057(95)00184-0
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of poly(ethylene oxide) with poly(acrylic acid-co-hydroxyethyl methacrylate)s

Abstract: Abstract-Random acrylic acid/hydroxyethyl methacrylate (AA/HEMA) copolymers were synthesized to study the influence of non-ionic (HEMA) structure defects introduced in poly(acrylic acid) on the complex formation with PEO (fiW 23200) at pH 3-3.5 in aqueous solution. Complex formation as studied with potentiometric titration (concentration 0.01-0.03 M monomer residues) was increasingly impeded when the molar ratio of HEMA to AA units in the polymers increased. Copolymers of AA and HEMA with molar ratios 30: 1, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 16 publications
(2 reference statements)
1
12
0
Order By: Relevance
“…This is supportive of the concept we have proposed that hydrogen bonding between the PAA and PEG networks serves to reinforce the network and prevent cracks from propagating, leading to an IPN with increased resistance to fracture at high strains. This is consistent with the work of Krupers et al 32 who first showed in solutions that the nature of the AA-based copolymer is important for complexation with PEG.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is supportive of the concept we have proposed that hydrogen bonding between the PAA and PEG networks serves to reinforce the network and prevent cracks from propagating, leading to an IPN with increased resistance to fracture at high strains. This is consistent with the work of Krupers et al 32 who first showed in solutions that the nature of the AA-based copolymer is important for complexation with PEG.…”
Section: Discussionsupporting
confidence: 93%
“…Since complexation in these systems occurs between hydrophilic acid groups of the PAA or PMAA with the oxygens on the PEG chain, the resultant interpolymer complex is more hydrophobic than the individual polymers alone. 29 The complexation between PEG and PAA has been verified experimentally by viscometry and potentiometry experiments, 13,14,[30][31][32] excimer fluorescence, 33,34 photon correlation spectroscopy, 35 solution microcalorimetry, 36 differential scanning calorimetry, Fourier-transform infrared spectroscopy, 37 and other fluorescence-based techniques. 31,38 The results shown in Fig.…”
Section: Discussionmentioning
confidence: 85%
“…If they are too large, the PEG molecules will completely cover the domains at any environmental conditions (see Supporting Information for details). In addition, PEG chains with degree of polymerization below 180 do not form complexes with PAA at the lower pH values (pH 3–3.5) 33…”
Section: Resultsmentioning
confidence: 96%
“…Copolymers and IPNs of two polymers that form hydrogen‐bonded complexes have been extensively studied 1, 19–27. These polymer complexes involve carboxyl groups (proton donors) and ether or amide groups (proton acceptors).…”
Section: Introductionmentioning
confidence: 99%